Optimization of Injection Pressure and Fuel Temperature in a Diesel Engine Using Biodiesel B40 - Romy, Romy; Suwitno, Suwitno; Ginting, Yogie Rinaldi; Sembiring, Ferdinandus Extranta (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2024)
Biodiesel is an alternative fuel substitute for diesel engines produced from vegetable or animal oil through the transesterification reaction process between fatty acid, methanol, and catalyst. However, in its use in diesel engines, there is a decrease in engine performance. This is partly due to the higher viscosity value compared to diesel. Some ways to improve engine performance using biodiesel include adjusting injection pressure and increasing fuel inlet temperature. This study aimed to determine the effect of adding injection pressure and fuel inlet temperature on the performance of diesel engines using B40, such as power, thermal efficiency, sfc, and AFR. This study used a 1-cylinder diesel engine with constant rotation, using five variations of injection pressure 110-150 bar with a 10 bar interval, and five variations of fuel inlet temperature 30˚C-70˚C with a 10˚C intervals, and five loads from 5,000 kg/m2 to 25,000 kg/m2 with a 5000 kg/m2 interval. Testing and data processing were done using the Taguchi method. The results showed that the best diesel engine performance occurred at an injection pressure of 150 bar and a fuel temperature of 60˚C. The predicted performance value achieved under optimal conditions is a power of 2.9 kW at a load of 25000 kg/m2, thermal efficiency of 69.92% at a load of 25000 kg/m2, sfc of 3 x10-5 kg/kJ at a load of 25000 kg/m2, and AFR of 169.23 at a load of 5000 kg/m2. Temperature significantly affects engine performance power, sfc, thermal efficiency, and AFR compared to injection pressure.